Determination and evaluation of the orbital transition methods between two elliptical earth orbits - Mahdi, Farid M.; Salih, Abdul-Rahman H.; Jarad, Majeed M. (Iraqi Journal of Science, 2020)
To transfer a satellite or a spacecraft from a low parking orbit to a geosynchronous orbit, one of the many transition methods is used. All these methods need to identify some orbital elements of the initial and final orbits as perigee and apogee distances. These methods compete to achieve the transition with minimal consumption of energy, transfer time and mass ratio consumed ), as well as highest accuracy of transition. The ten methods of transition used in this project required designing programs to perform the calculations and comparisons among them. The results showed that the evaluation must depend on the initial conditions of the initial orbit and the satellite mechanical exception as well as the target orbit. The most efficient methods of transition in terms of energy required were, sequentially, methods 10, 1, 8, 9, and 2, whereas the least efficient in terms of energy consumption, fuel and transition time were, sequentially, methods 5,6, and 7. Method 3 was the most efficient when the orbit needed to change the inclination with the transition. The first phase of multi-stage transition is the most energy consuming.